i have solved this problem and got same answer as given but in intermediate steps my approach was different:

i took Pbottom of drop=Ptop of drop+pgh
in book they took Ptop=Pbottom of drop+pgh
which is correct???

3 Answers

seoni ·

u'r right,,

but pls tell how to eliminate 'r1.r2'?

kaymant ·

We have (see figure)
p1 - p3 = 2SR1 and
p2 - p4 = 2SR2
Also, p3 = p4 = patm and
p2 = p1 + ρgh
So we get
ρgh = 2S (1R2 - 1R1)
which gives the difference in curvatures as
R1 - R2 = ρghR1R22S

Vivek @ Born this Way ·

Nice sir!

Your Answer

Close [X]